A fluorescent probe for the specific detection of cysteine in human serum samples. Issue 26 (17th June 2019) - Huang, Zhen; Wu, Cuiyan; Li, Yaqian; Zhou, Zile; Xie, Ruihua; Pang, Xiao; Xu, Hai; Li, Haitao; Zhang, Youyu
Abstract : A turn-on fluorescent probe for cysteine with high selectivity was designed and synthetized. The probe can be used for "naked-eye" detection of Cys with an obvious color change from yellow to colorless. The probe could be applied for Cys detection in real human serum. Abstract : Serum cysteine (Cys) level is correlated with many diseases. Therefore, it is very important to detect the concentration of serum cysteine with high sensitivity and accuracy. In this study, a turn-on fluorescent and colorimetric probe, ( E )-2-(2-(4-formylstyryl)-4 H -chromen-4-ylidene)malononitrile, termed as probe1, was designed and synthesized for the detection of Cys in serum. Upon the addition of Cys, a remarkable enhancement in the fluorescence feature at 440 nm and a significant colour change of the probe solution were observed. Under optimal conditions, the probe enables quantitative analysis of Cys with high sensitivity. Moreover, the detection limit of Cys was calculated as 63 nM. The results showed that the fluorescence response of probe1 to cysteine was highly selective when homocysteine (Hcy), glutathione (GSH) and other natural amino acids coexisted with cysteine under physiological conditions. Furthermore, the probe1 could be used to accurately and sensitively detect cysteine in human serum.